Concentrated Growth Factor - Review - Kavitha, Prof.Dr.M.; Kathiravan, Dr.S. (Journal of Biomedical and Pharmaceutical Research, 2018)
Regenerative medicine is one of the most dominant objectives of today’s rehabilitation therapies. Growth factors are bioactive proteins which control the process of wound healing. Platelet concentrates are rich in growth factors enhancing wound healing process and promotes regeneration of bone. One such platelets concentrates is Platelet Rich Fibrin (PRF) a second generation platelet derivative used widely for bone healing. And in 2006 Sacco introduced advanced second generation platelet derivative Concentrated Growth Factor (CGF), which showed enhanced bone healing capacity, higher tensile strength; more growth factors, higher viscosity and higher adhesive strength than PRF . Recently more importance has been given to CGF for its excellent biological activity and predictable method of preparation, their by findings its way in the field of regeneration. Key words: Concentrated Growth Factors, Platelet Rich Fibrin, regeneration, growth factors.